SCIENTIFIC PUBLICATIONS IN COUNTRIES AROUND THE WORLD: BIBLIOMETRIC ANALYSIS OF ISLAM ECONOMICS - Indrawati, Andi; Latif, Imam Nazarudin; Yudhyani, Eka; Heryanto, Heryanto (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
This study's objective is to map research data pertaining to Islamic economics. This research was undertaken by examining the Scopus database and Google Scholar. The researcher utilized the keyword "Islamic economics" to generate more specific searches under the headings Article Title, Abstract, and Keywords. The researcher employed a quantitative descriptive technique and bibliometric analysis for this investigation. Based on the search results, the researcher received 993 papers from the publishing years 1963 to 2020. The search for scientific papers was then reduced to solely using two types of document documents, articles and conference papers. via means of Harzing's PoP (Publish Of Perish) Researchers also found that the topic of Islamic Economics in collaboration between countries was still very large, the researcher also found that many universities in various countries participated in the topic of google scholars